STRATEGI PENGEMBANGAN OBJEK WISATA BUKIT CAMBAI KABUPATEN SOLOK - Adrian Eka Putra; Syafri Anwar (JURNAL BUANA, 2021)
This study aims to describe: (1) the internal factors of the Bukit Cambai tourist attraction in influencing tourist visits (2) The external factors of the Bukit Cambai tourist attraction in influencing tourist visits (3) The appropriate development strategy to be applied in influencing tourist visits. This type of research is descriptive with a qualitative approach. The research subjects were determined based on purposive sampling. Data collection techniques by observation, interviews, and documentation. Data analysis techniques by data collection, data reduction, data presentation, drawing conclusions / verification and SWOT analysis. The results showed (1) the main internal factors in terms of strength: the uniqueness and beauty of the object which is the main attraction, in terms of weaknesses: the condition of the road that has been damaged. (2) The main external factor in terms of opportunities: increase in people's economic income, in terms of threats: cessation of funding from the government. (3) The right strategy for the development of the Bukit Cambai tourism object is (1) Optimizing the resources owned, (2) Improving the quality of tourism management (3) Utilizing technology in promotional activities.